Architectures for scalable integrated photo driven catalytic devices-A concept study. (7th December 2016) - Kirner, Simon; Bogdanoff, Peter; Stannowski, Bernd; van de Krol, Roel; Rech, Bernd; Schlatmann, Rutger
Abstract: Architectures with various degrees of integration are investigated for water splitting devices using the energy of light for fuel production. The many approaches presented in literature for such 'photo driven catalytic (PDC) devices' are reviewed and discussed in perspective of their scalability to large area. Then, back-of-the-envelope type techno-economic considerations for such systems are presented. Compared to the benchmark, consisting of large electrolyzers coupled to the grid, it was found that PDC devices could be competetive in places with high irradiation, given the assumption that no compromises on system stability have to be made compared to stand-alone PV-systems for electricity generation. In agreement with literature, it was found that the cost of the PV part dominate the hydrogen generation costs, based on today's technology. Thus, device architectures that allow low cost PV (by e.g. avoiding use of costly materials or introducing further inherent loss mechanisms) are considered the most promising ones. Highlights: A classification is given for photo driven catalytic device architectures with advantages and disadvantages for upscaling. Techno-economic calculations are presented, highlighting the advantages of certain architectures over others. Integrated devices have cost advantages over systems with DC/DC inverters if no compromises on lifetime has to be made. The difficulties are pointed out to obtain high fraction of active area and low series resistance losses at the same time.